Energetically Optimal Trajectory for a Redundant Planar Robot by Means of a Nested Loop Algorithm - Urrea-Onate, E; Kern-Molina, J; Gonzalez-Romero, G (Kauno Technologijos Universitetas, 2022)
This work presents an optimal point-to-point trajectory planning method based on fourth degree polynomials to reduce the energy consumption of a redundant planar robot in the XY plane. The contribution of this study focuses on the development of a two-level nested optimization algorithm, which manages to optimize three elements: the Optimal Weighting Vector that establishes the influence of each joint on the total energy consumption of the robotic equipment; the optimal start and finish configurations of the trajectory; and the vector corresponding to the fifth coefficient of the trajectory generator polynomial. The tests are carried out with different optimization techniques and objective functions related to energy consumption to determine their best combination and achieve the minimum possible computation time and energy savings, according to the test conditions used. Furthermore, the energetic performance of the redundant manipulator is compared with its non-redundant version, limiting its operation to only two degrees of freedom in all its variants. © 2022 Kauno Technologijos Universitetas. All rights reserved.